An informative review on recent development of renewable energy system. Issue 3 (3rd April 2022) - Gandhar, Abhishek; Vijay, Sanyam; Mohapatra, Aryan; Datta, Jeet; Shukla, Shiv
Abstract: Renewable resources have always been seen a sustainable solution for our energy needs, and many sources have been discovered over the course of last century, and many ways have been put forward to harness energy from these sources and used for greater good. The development is still going on and will go on to find more efficient ways of extracting the energy out of these sources. This paper tries to give a view of the current ongoing research in this area for different-different energy sources through authoring this paper to understand the ongoing trend and the future possibilities and what successes have been achieved in this arena. In this paper, many papers have been reviewed on the recent development in renewable energy system in last 20 years and papers to review have been taken from globally reputed conferences and journals. Various technology/energy systems and trend over the course for various sources have been studied and the authors have put forward the results as their conclusions.